Economic Issues with Milling Hard White Wheat - Boland, Michael; Dhuyvetter, Kevin C. (My University, 2005)
This publication discusses the economic impliactions with milling hard white wheat in Kansas.
MF2499_2002_05
Keywords: MF2499; MF